Grievance Initiation and Resolution. A Test of the Behavioural Theory - Gandz, Jeffrey (Relations industrielles / Industrial Relations, 1979)
The Author puts Walton and McKersie's behavioural theory of labour negotiations to test in a study of a non-random sample of 118 bargaining units